Home Sweet Home: Entrepreneurs' Location Choices and the Performance of Their Ventures - Dahl, Michael S.; Sorenson, Olav (Management Science, 2012)
Entrepreneurs, even more than employees, tend to locate in regions in which they have deep roots (“home” regions). Here, we examine the performance implications of these choices. Whereas one might expect entrepreneurs to perform better in these regions because of their richer endowments of regionally embedded social capital, they might also perform worse if their location choices rather reflect a preference for spending time with family and friends. We examine this question using comprehensive data on Danish start-ups. Ventures perform better—survive longer and generate greater annual profits and cash flows—when located in regions in which their founders have lived longer. This effect appears substantial, similar in size to the value of prior experience in the industry (i.e., to being a spin-off). This paper was accepted by Gérard P. Cachon, organizations.